Hubungan Ilmu dengan Nilai-Nilai Hidup Manusia Sebagai Basis Pengembangan Teori dan Konsep dalam Kajian Manajemen Pendidikan Islam - Alamsyah, Farhan; Fathurahman, Meiduari; Subekti, Imam (Journal of Educational Review and Cultural Studies, 2024)
Islamic education plays a crucial role in shaping a quality Muslim generation, capable of facing future challenges, and aligned with Islamic values. This study aims to analyze the relationship between knowledge and human life values, as well as the role of knowledge and humans in the development of theories and concepts in Islamic education management. The approach used in this research is qualitative with a literature study method. The findings indicate that knowledge in Islam is not only a tool for achieving worldly and hereafter success but also serves to develop human life values such as tawakkal (trust in God), akhlak (morality), and ikhlas (sincerity). Knowledge plays a role in the formation of concepts and theories of Islamic education management, which integrates Islamic ethical, moral, and aesthetic values into the educational process. The application of knowledge in Islamic education management aims to create effective and sustainable education, as well as to shape individuals with Islamic character. Therefore, Islamic education management focuses not only on educational theories but also on the practice of Islamic values that improve the quality of life and character of the students. This study concludes that knowledge and Islamic education serve dual purposes: as a tool for intellectual advancement and as a means for forming quality spiritual and moral development.